S. J. Quincy (Editor), Revised Ordinances of the City of Sioux City, Iowa 62 (1882), Public Safety, § 4 - (:unkn) unknown (General Publisher, 1882)
Prohibited the carrying a concealed pistol, revolver, slungshot, cross-knuckles, knuckles of lead, brass or other metal, or any Bowie knife, razor, billy, dirk, dirk knife or Bowie knife, or other dangerous weapon.
--
Keywords: CARRY - CONCEALED